International Capital Markets, 1986. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1986)
This paper provides a description and analysis of recent developments in international capital markets and an assessment of the prospects for private financing flows. It focuses particularly on recent trends in liberalization and innovation in international financial markets, including relevant changes in supervision, and on developments in the debt situation, especially the factors that influence flows to developing countries. The pattern of current account imbalances among industrial countries, which have well-developed securities markets, has been a major factor in the shift of international financial flows toward international bond markets and away from the bank credit market. This shift would be even more apparent if foreign purchases in domestic bond markets were also incorporated. The increase in the swap market has been complemented by an expansion of the futures and options markets. These short-term hedging and arbitrage instruments have increased the scope for banks and nonbanks to cover financial risks associated with fluctuations in exchange and interest rates.